Safe but fragile: Information acquisition, sponsor support and shadow bank runs - Philipp J. König; David Pothier (Deutsche Bundesbank, 2018)
This paper proposes a theory of shadow bank runs in the presence of sponsor liquidity support. We show that liquidity lines designed to insulate shadow banks from market and funding liquidity risk can be destabilizing, as they provide them with incentives to acquire private information about their assets' type. This can lead to inefficient market liquidity dry-ups caused by self-fulfilling fears of adverse selection. By lowering asset prices, information acquisition also reduces shadow banks' equity value and may spur inefficient investor runs. We compare different policies that can be used to boost market and funding liquidity. While debt purchases prevent inefficient dry-ups, liquidity injections may backfire by exacerbating adverse selection frictions.
Keywords: D82; G01; G20; 330; Information Acquisition; Adverse Selection; Bank Runs; Global Games